Driveline Features as Risk Factor for Infection in Left Ventricular Assist Devices: Meta-Analysis and Experimental Tests - Kranzl, Melanie; Stoiber, Martin; Schaefer, Anne-Kristin; Riebandt, Julia; Wiedemann, Dominik; Marko, Christiane; Laufer, Günther; Zimpfer, Daniel; Schima, Heinrich; Schlöglhofer, Thomas (Frontiers in Cardiovascular Medicine, 2021)
Background: Risk factors for driveline infection (DLI) in patients with left ventricular assist devices are multifactorial. The aim of this study was to analyze the correlation between mechanical driveline features and DLI occurrence. Methods: A meta-analysis was conducted that included studies reporting DLI rates at 6 months after implantation of any of three contemporary devices (HVAD with Pellethane or Carbothane driveline, HeartMate II, and HeartMate 3). Further, outer driveline diameter measurements and ex-vivo experimental three-point bending and torsion tests were performed to compare the stiffness of the four different driveline types. Results: 21 studies with 5,393 patients were included in the meta-analysis. The mean weighted DLI rates ranged from 7.2% (HeartMate II) to 11.9% (HeartMate 3). The HeartMate II driveline had a significantly lower maximal bending force (Loadmax) (4.52 ± 0.19 N) compared to the Carbothane HVAD (8.50 ± 0.08 N), the HeartMate 3 (11.08 ± 0.3 N), and the Pellethane HVAD driveline (15.55 ± 0.14 N) (p < 0.001). The maximal torque (Torquemax) of the HeartMate II [41.44 (12.61) mNm] and the Carbothane HVAD driveline [46.06 (3.78) mNm] were significantly lower than Torquemax of the Pellethane HVAD [46.06 (3.78) mNm] and the HeartMate 3 [95.63 (26.60) mNm] driveline (p < 0.001). The driveline of the HeartMate 3 had the largest outer diameter [6.60 (0.58) mm]. A relationship between the mean weighted DLI rate and mechanical driveline features (Torquemax) was found, as the the HeartMate II driveline had the lowest Torquemax and lowest DLI rate, whereas the HeartMate 3 driveline had the highest Torquemax and highest DLI rate. Conclusions: Device-specific mechanical driveline features are an additional modifiable risk factor for DLI and may influence clinical outcomes of LVAD patients.